An Analysis of Closed Caption Accessibility and the Inclusive Viewing Experience of the Deaf Community on Netflix - Ghazy Arkan, Haidar; Nurcahyo, Dedi Eko; Aulia, Farhana (Dinasti International Journal of Education Management and Social Science, 2025)
This study analyzes the accessibility of closed captioning (CC) to the inclusive viewing experience of the Deaf community on the Netflix streaming service in Indonesia. Departing from the gap between feature availability and perceived functionality, this study positions Deaf people as subjects of knowledge, not merely objects of the service. Qualitative-descriptive methods were used through in-depth interviews and observations of viewing practices. The study population was the Deaf community in the DKI Jakarta and Tangerang areas, with a convenience sampling technique involving six respondents as participants in the observations and interviews. Data were analyzed thematically with a focus on time synchronization, translation accuracy, descriptions of sound effects/emotions, readability, and consistency of caption placement. The results of this study include a map of accessibility dimensions (technical, cognitive, affective, and social), identification of common barriers and good practices, and recommendations for improving Closed Caption (CC) standards and interface design that involve the participation of the Deaf community from the upstream production stage. The theoretical contribution enriches the discourse on inclusive communication and digital literacy, while the practical contribution provides a basis for policy and technical guidelines for platform providers, policymakers, and educators. Ultimately, this study affirms everyone's right to enjoy stories equally safely, meaningfully, and without barriers.